Practical tips for teaching the undifferentiated medical student in the emergency department [version 2; peer review: 2 approved] - Dimitrios Papanagnou; Allan D. Winger (MedEdPublish)
Emergency medicine clerkships have become more prevalent in the third year of medical school, a time when students are immersed in the core clinical training of their undergraduate medical education. There is little guidance for clinician educators, however, on how to effectively scaffold learning for third-year medical students when rotating in the emergency department (ED) during core clerkships. The authors sought to provide best practices in teaching to leverage the rich learning environment of the ED – regardless of their specialty selections. Based on an extensive review of the literature spanning on-shift teaching, feedback, clinical medicine, and bedside teaching, the following twelve tips are offered to guide the instruction of the undifferentiated third-year medical student in the ED.